Financial Knowledge, Inclusivity, and Sustainability: MSMEs in Denpasar with Financial Effectiveness Mediator - Tahu, Gregorius Paulus (Jurnal Manajemen, 2025)
This study investigates the extent to which financial literacy and access to financial services influence the performance and sustainability of MSMEs in Denpasar. The research involved 150 MSME operators using a bootstrapping approach and a 5 per cent significance level. The findings reveal that both financial literacy and financial inclusion positively impact financial performance. However, only financial inclusion shows a significant direct effect on business sustainability, while financial literacy does not. Financial performance serves as a mediating variable, particularly in linking financial literacy to MSME sustainability, indicating full mediation since the direct effect is not significant. In contrast, financial inclusion demonstrates partial mediation, with both direct and indirect effects being statistically significant. These results emphasize the importance of enhancing financial knowledge and expanding access to financial services, alongside strengthening financial performance, to support the long-term sustainability of MSMEsfinancial inclusion, and improving financial performance to strengthen MSME sustainability.